Exclusive breastfeeding for 4 versus 6 months and growth in early childhood. - Jonsdottir, OH; Kleinman, RE; Wells, JC; Fewtrell, MS; Hibberd, PL; Gunnlaugsson, G; Thorsdottir, I (2014)
To investigate the growth and the prevalence of overweight in early childhood among infants exclusively breastfed for 6 months (EBF) compared with those receiving complementary foods from 4 months of age in addition to breast milk (CF).